Motivación y desempeño laboral de los colaboradores de CSM Corporación Oriente S.A.C. Iquitos 2025 - Alvarado Nuñez, Susan Jackelin (2025)
The research aimed to determine the relationship between motivation and job performance of employees at CSM Corporación Oriente S.A.C., Iquitos – 2025. The study was developed using a quantitative approach, applied type, correlational level, and non-experimental design, with a population of 50 employees, who were surveyed through a questionnaire as a data collection instrument. The results concluded that motivation within the company is high, as employees always feel enthusiastic, engaged in their tasks, and believe that rewards are fair, although it was noted that recognition for their achievements is only occasionally given. On the other hand, job performance is rated as optimal, since responsibilities are always fulfilled effectively and tools and technologies are used efficiently, although there are weaknesses in detailed planning and consistent supervision. Finally, it was determined that there is a significant relationship between motivation and job performance, as evidenced by a Pearson correlation coefficient of 0.766 p=0.002, indicating that higher levels of motivation contribute to better performance in the workplace.